2021
DOI: 10.1038/s41420-021-00709-4
|View full text |Cite
|
Sign up to set email alerts
|

Over-expression of lncRNA TMEM161B-AS1 promotes the malignant biological behavior of glioma cells and the resistance to temozolomide via up-regulating the expression of multiple ferroptosis-related genes by sponging hsa-miR-27a-3p

Abstract: A growing body of evidence suggests that long-chain non-coding RNA (lncRNA) plays an important role in the malignant biological behavior and drug resistance of glioblastoma (GBM) cells. In this study, we analyzed the role and potential mechanism of lncRNA TMEM161B-AS1 in the malignant biological behavior of GBM cells and temozolomide (TMZ) resistance. Studies have found that FANCD2 and CD44 are significantly related to the occurrence of GBM, TMZ resistance and the survival of GBM patients. Knockdown of TMEM161… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 56 publications
0
25
0
Order By: Relevance
“…Several lncRNAs were found to be associated with ferroptosis in gliomas. LncRNA TMEM161B-AS1 was identified to promote the malignant behavior and temozolomide resistance through enhancing the expression of multiple ferroptosis-related genes ( 44 ). However, we did not validate the expression of lncRNAs screened by RNA-seq using experimental methods.…”
Section: Discussionmentioning
confidence: 99%
“…Several lncRNAs were found to be associated with ferroptosis in gliomas. LncRNA TMEM161B-AS1 was identified to promote the malignant behavior and temozolomide resistance through enhancing the expression of multiple ferroptosis-related genes ( 44 ). However, we did not validate the expression of lncRNAs screened by RNA-seq using experimental methods.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the ferroptosis pathway can induce cancer cell death, especially in the case of drug resistance, and enhance the sensitivity of tumours to chemotherapeutic drugs ( 68 ). Studies have shown that TMZ combined with erastin can significantly improve antitumor activity, which reflects the importance of ferroptosis in the treatment of gliomas ( 31 , 69 , 70 ). Our experiments confirmed that knockdown of PELATON enhanced the sensitivity of GBM cells to erastin and inhibited the proliferation of tumour cells.…”
Section: Discussionmentioning
confidence: 99%
“…The results have been confirmed in other studies. Chen Q. et al (2021) found that lncRNA TMEM161B-AS1 mediated by HSA-Mir-27a-3p had an inhibitory effect on glioma cells, and hsa-Mir-27a-3p inhibited the proliferation, migration, and invasion of glioma cells by down-regulating the expression of FANCD2 and CD44, thus promoting cell apoptosis and ferroptosis. This supports that miR-27a-3p can target TMEM161B-AS1.…”
Section: Discussionmentioning
confidence: 94%